Theory of Penis Envy: a critique of the notion of women’s inferiority in psychoanalysis (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
Abstract The article critically examines Freud’s theory of penis envy from a gender perspective, emphasizing Karen Horney’s contributions and the need for a more inclusive psychoanalytic interpretation of female subjectivity.
Keywords: penis envy; Karen Horney; Freud; femininity; critical psychoanalysis